2013
DOI: 10.1353/pla.2013.0017
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Demographics: Assessing Library Use Across the Institution

Abstract: In Fall 2011, staff at the University of Minnesota Libraries-Twin Cities undertook a project to measure how often, and in what ways, students used the Libraries' services. Partnering with the University's Office of Institutional Research, the team investigated ways to match library service usage to individual accounts while retaining patron privacy to determine who was-and was not-using the library. With complete data sets, the group was able to determine overall usage rates for undergraduate and graduate stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…In some cases, findings are relatively consistent across studies: for example, arts and humanities are usually found to be the biggest users of library materials (De Jager, 2002;Maughan, 1999;Whitmore, 2002). Nackerud et al (2013) found, at a more granular level, that College of Design undergraduates were the highest library borrowers in their study. But in other instances, different ways of defining subjects and user groups can lead to confusion in understanding exactly how findings may apply in other settings.…”
Section: Literature Reviewmentioning
confidence: 87%
See 2 more Smart Citations
“…In some cases, findings are relatively consistent across studies: for example, arts and humanities are usually found to be the biggest users of library materials (De Jager, 2002;Maughan, 1999;Whitmore, 2002). Nackerud et al (2013) found, at a more granular level, that College of Design undergraduates were the highest library borrowers in their study. But in other instances, different ways of defining subjects and user groups can lead to confusion in understanding exactly how findings may apply in other settings.…”
Section: Literature Reviewmentioning
confidence: 87%
“…But in other instances, different ways of defining subjects and user groups can lead to confusion in understanding exactly how findings may apply in other settings. For example, many studies found engineering students to be the least engaged library users across resources (Kramer & Kramer, 1968;Bridges, 2008;Cox & Jantti, 2012;Nackerud et al, 2013). However Chrzastowski and Joseph (2006) found that graduate students from the physical sciences and engineering used online resources more than graduates in other disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an issue noted in studies, such as "Analyzing Demographics" by Nackerud et al 29 Most of these studies have taken place at medium-to largesized institutions. The assessment model in this research uses a research tool common to a wide range of institutional types and sizes because it is less labor and technology intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Wood and Walther (2000) reminds us that, although there is a wealth of free information on the Internet, the profit motive remains strong for publishers, and patrons will need libraries to receive free access to subscription material. Nackerud, Fransen, Peterson, and Mastel (2013) collected demographic data on licensed database, e-journal, and e-book usage and website logins at the University of Minnesota via a "click-thru" script, and found that 65% of undergraduates used electronic resources or logged into the website, while 82% of graduate students did so. Marek (2011) offers comprehensive advice on setting up and using web analytics in a library.…”
Section: Literature Reviewmentioning
confidence: 99%